Foreign Bodies in Otorhinolaryngology: A Study of 128 Cases - Silva, Breno Simões Ribeiro da; Souza, Leandro Oliveira; Camera, Marcela Gonçalves; Tamiso, Arnaldo G. Braga; Castanheira, Luiz Vicente Rizzo (International Archives of Otorhinolaryngology, 2009)
Introduction: The occurrence of foreign bodies in otorhinolaryngology is a cause of frequent consultations in the urgency service. Objective: The objective of this work is to describe a number of patients with foreign bodies, as well as to evaluate the clinical picture and the treatment of these cases. Method: We carried out a prospective study of 128 patients with diagnosis of nose, ear and oropharynx foreign body, attended in the emergency room of the Hospital Paulista de Otorrinolaringologia, São Paulo, in the period from August 2005 through august 2007. Results: They were 67.18% of cases of foreign body in the ear; 18.75% cases in the nasal cavity and 14.07% in the oropharynx. Out of these patients 55.47% were men and 44.53% were women. The mean age was of 17 years. The evolution time average was of 12.2 days, and 57.03% of the cases were attended with less than 24 hours of evolution. From the total of patients, 64.85% received initial service in the Emergency Room of the Hospital and 35.15% had been sent from another service after some previous removal attempt. The most common symptom of the cases of foreign body in the oropharynx was odinophagia, which was present in 88.88% of the cases; of foreign body in the nose, unilateral rhinorrhea, present in 37.5% of the cases and cacosmia in 25% of the cases; and in the foreign body in the ear, 39.53% evolved with hypacusis. Conclusion: Most of the cases with prior manipulation for removal of the foreign bodies by non-skilled professional or laymen evolved with complications.